REKAYASA PERANGKAT LUNAK PROGRAM APLIKASI MANAGEMENT SERVISE STATION PT.BUANA CENTRA SWAKARSA LOGISTICS (BCS-LOGISTICS) CILEGON - Rizki Fatullah; Dedi Juniansha (Journal of Innovation And Future Technology (IFTECH), 2019)
Management service station program implemented at PT. BCS Logistics. Management Service Station is a major supporting factor for PT. BCS Logistics in meeting the needs for vehicle repair services, but in its activities the Management Service Station experiences obstacles in coordinating vehicle repair requests from other related divisions. This is because the application program used still uses the single user method so that the information needed by the service station seems slow and inefficient. For this reason, an integrated management is needed so that the information needed by the relevant division can be quickly conveyed and the service station can be responsive to service vehicle repairs. To overcome these obstacles needed an application program that is integrated with the web-based multi-user program method in the service station division to arrange the coordination of requests for repairs, identification of vehicle repairs and requests for spare parts. With this application the divisions related to service stations can access and get information directly, quickly, and the data is stored properly that is used for data collection vehicle repair history is still feasible or not to be operated. Application Management Service Station Program is also very concerned in improving the work system that is applied so that all transactions that occur can be easily monitored.